Maize value chain analysis: A case of smallholder maize production and marketing in selected areas of Malawi and Mozambique - Mango, Nelson; Mapemba, Lawrence; Tchale, Hardwick; Makate, Clifton; Dunjana, Nothando; Lundy, Mark M. (Informa UK Limited, 2018)
This article analyzes maize value chain performance in Malawi and Mozambique using data collected from a market study commissioned by the International Centre for Tropical Agriculture. The results show that although smallholder maize productivity is slightly higher in Malawi, a maize value chain analysis indicates that smallholder maize in Mozambique is more competitive. Mozambique has a relatively higher competitive advantage with regard to maize production because of the relatively lower input costs, perhaps due to its proximity to the coast, which invariably reduces input costs relative to its land-locked neighbor, Malawi. However, smallholder maize productivity is low in both countries, when compared to the regional average. The article concludes that interventions aimed at raising smallholder productivity would invariably make smallholder farmers more competitive. It proposes policy implications aimed at raising the productivity and trade competitiveness of maize, as this will ensure the overall productivity of the maize-based smallholder farming system in the two countries.